1994
DOI: 10.1136/jnnp.57.7.805
|View full text |Cite
|
Sign up to set email alerts
|

Relation of anosognosia to frontal lobe dysfunction in Alzheimer's disease.

Abstract: A self-rating scale of memory functions was administered to 24 non-depressed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
174
6
18

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(204 citation statements)
references
References 26 publications
6
174
6
18
Order By: Relevance
“…Previous studies have suggested the presence of depression in the patient and informant can affect the degree of discrepancy between raters (Rubenstein et al, 1984;Epstein et al, 1989;O'Conner et al, 1990;Bolla et al, 1991). Finally, some authors have suggested that executive functioning or frontal lobe functioning may be particularly associated with a loss of awareness of deficit that can lead to discrepancies in self-vs other-reporting (Reed et al, 1993;Michon et al, 1994). The current study lacked a measure of higher-order reasoning and problem solving and this should be included in future research.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous studies have suggested the presence of depression in the patient and informant can affect the degree of discrepancy between raters (Rubenstein et al, 1984;Epstein et al, 1989;O'Conner et al, 1990;Bolla et al, 1991). Finally, some authors have suggested that executive functioning or frontal lobe functioning may be particularly associated with a loss of awareness of deficit that can lead to discrepancies in self-vs other-reporting (Reed et al, 1993;Michon et al, 1994). The current study lacked a measure of higher-order reasoning and problem solving and this should be included in future research.…”
Section: Discussionmentioning
confidence: 88%
“…However, there are now a number of studies showing that within dementia samples, self-report often differs substantially from information collected from caregivers (DeBettignies et al, 1990) and does not correspond to objective measures of cognitive functioning (Michon et al, 1994;Tierney et al, 1996). However, there is substantial variability in the degree to which dementia patients and their caregivers differ (Reed et al, 1993;Michon et al, 1994). It is not yet clear to what degree patient or informant characteristics and/or relationship variables influence this difference.…”
Section: Introductionmentioning
confidence: 99%
“…Anosognosia in AD subjects was associated, in some but not all studies, with memory impairment, reflected, for example, by intrusions (i.e., erroneous selection of non-target items) in recognition tasks (Reed et al, 1993;Dalla Barba et al, 1995). A relationship was frequently suggested between lack of awareness of cognitive dysfunction and impairment in specific ''frontal'' tests (Lopez et al, 1994;Michon et al, 1994;Dalla Barba et al, 1995;Ott et al, 1996). All those parameters may be viewed as confounding factors, that contribute to, but do not yet explain, anosognosia in dementia.…”
Section: Behavioral Measures Of Anosognosia In Admentioning
confidence: 99%
“…Las perturbaciones de la presencia de anosognosia en los pacientes con EA tienen una gran repercusión en el inicio de la enfermedad y, en algunos pacientes, es una de las principales manifestaciones asociadas al fenotipo de la EA inicial 24 . En estos casos, la presencia de anosognosia y los cambios de conducta pueden tener mayor repercusión para el paciente y el entorno que la propia pérdida de memoria o la discapacidad funcional 25 .…”
Section: Discussionunclassified